CORAL BLEACHING, KARANG HIDUP ATAU MATI? - Qinthan Azzahra Aulia; Ni Wayan Purnama Sari (OSEANA, 2020)
Coral reef ecosystem is one of the coastal marine ecosystems in tropical waters. Coral reef ecosystems are vulnerable to damage mainly due to environmental factors. A fairly popular event of coral reef damage is coral bleaching. Mass coral bleaching is generally caused by changes in Sea Surface Temperature (SST). The condition of corals that have bleaching is different from the condition of corals that have died. The recovery process from coral bleaching phenomena can be effectively carried out if the surrounding environment is supportive and sea surface temperature return stable. The phenomenon of coral bleaching is a real indicator of the environmental stresses that occur on coral reefs. This paper will explain about coral bleaching, the factors that cause coral bleaching, and whether the bleaching coral reefs mean alive or dead.